2012
DOI: 10.1007/s00441-012-1361-4
|View full text |Cite
|
Sign up to set email alerts
|

BMPRIB and BMPRII mRNA expression levels in goat ovarian follicles and the in vitro effects of BMP-15 on preantral follicle development

Abstract: This study evaluated the levels of bone morphogenetic protein receptors BMPRIB and BMPRII mRNA in goat follicles and the effects of bone morphogenetic protein-15 (BMP-15) on the in vitro development of cultured preantral follicles. Real-time polymerase chain reaction (PCR) was used to analyze the levels of BMPRIB and BMPRII mRNA in caprine preantral follicles and in small and large antral follicles. Preantral follicles (≥150 μm) were also isolated from goat ovaries and cultured for 18 days in α-MEM(+) suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…Similar studies showed that Lima et al. () assessed the caprine isolated preantral follicles during 18 days of in vitro culture with BMP‐15 (50 ng/ml) and found stimulation in the growth, antrum formation and ultrastructural integrity. Magalhães et al.…”
Section: Discussionsupporting
confidence: 66%
“…Similar studies showed that Lima et al. () assessed the caprine isolated preantral follicles during 18 days of in vitro culture with BMP‐15 (50 ng/ml) and found stimulation in the growth, antrum formation and ultrastructural integrity. Magalhães et al.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, Sp-BMPRIB and Sp-BMPRII had an abundant expression in ovary as well as Sp-BMP7. The higher expression of some BMP ligands and receptors in ovary has been reported in many mammals, such as goat (Lima et al, 2012), hamster (Lima et al, 2012) and swine (Zhao et al, 2014). Thus, the results of tissues distribution, especially the abundant expression of BMP system in ovarian development attracted our attention.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro follicle culture is an effective tool to detect the mechanisms of interaction oocyte, granulosa cell and theca cell. Many culture systems of follicle have been developed in different species [2], [3], [4], [5], [6], [7]. Although the fertilizable oocytes have been developed from mouse primordial and early preantral follicles in vitro [8], [9], [10], the follicle culture system for assaying the mechanism of preantral follicular development is still unstable.…”
Section: Introductionmentioning
confidence: 99%